Happy Hypoxemia In COVID-19 - Ilham; Deddy Herman; Russilawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
The new coronavirus disease 2019 (COVID-19) pandemic is becoming a global health crisis that challenges health systems around the world. The clinical spectrum of COVID-19 varies from mild upper respiratory tract infections to severe pneumonia and acute respiratory distress syndrome, but there are also many patients present with an SpO2 < 90% but without symptoms of shortness of breath. This phenomenon is called happy hypoxemia or silent hypoxemia. Shortness of breath or dyspnea is a subjective sensation resulting from inadequate breathing effort and is usually described as constriction in the chest, difficulty breathing air or difficulty breathing. Breathing is controlled centrally by the respiratory center in the medulla oblongata and the pons region which controls the "respiratory drive" and adapts respiration to the body's metabolic needs. The mechanisms that play a role in this phenomenon include the presence of intrapulmonary shunts, loss of pulmonary perfusion regulation, vascular microthrombus and impaired pulmonary diffusion capacity.